Revolutions in Military Affairs (RMA) Policy in Countering the Threat of Terrorism and Cyber Crime in Singapore - Indrawan, Jerry; Zahira, Azila (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
As a country located in the Southeast Asia Region with a very small area flanked by several major regional powers, Singapore is vulnerable to symmetrical and asymmetrical threats. If Singapore does not develop its military capabilities, there will be more threats to its people. Many asymmetrical threats experienced by Singapore are cyber attacks, both terrorism and cyber crime. This is because Singapore is a developed country with a growing economy, and has advanced information and technology infrastructure, which makes it digitally vulnerable. In addition, Singapore has good relations with Western countries that make it an easy target for acts of terrorism, especially in Southeast Asia, which is known for its massive affiliation with global terror groups. The author uses a descriptive qualitative method by searching for data through books, journals, online literature, and other supporting data. The purpose of writing this research is to find out how Singapore's RMA policy deals with the threat of terrorism and cybercrime